A community for students.
Here's the question you clicked on:
 0 viewing
angela210793
 5 years ago
Simplify:
1a+bab

ba +a
angela210793
 5 years ago
Simplify: 1a+bab  ba +a

This Question is Closed

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0\[\frac{1a+ba+b}{ba+a} = \frac{12a + 2b}{b}\] all you've got to do is simplify by multiplying the sign to the values in brackets and compute ^_^

angela210793
 5 years ago
Best ResponseYou've already chosen the best response.0those aren't brackets :):):):) absolute value :S

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0hmm , oh right, you're right lol. If you have absolute values, then the signs switch.

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0not sure how though? >_< I'm sorry. I know that ba = ab

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0but not sure of the one in the denominator.

angela210793
 5 years ago
Best ResponseYou've already chosen the best response.0i'm not sure how to solve this 2.....thnx a lot anyway :) ^_^

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Alright, let me see if I can make it simpler, 4x = 4x, 4x = 4x 4x3= 34x 2a +b = 2a+b makes any sense?

angela210793
 5 years ago
Best ResponseYou've already chosen the best response.0yea it does...thnx :)so i just switch signs...nothing else?

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0looks like it :) np dear ^_^

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0you switch signs only when you have a negative inside with another variable, others stay the same ^_^

angela210793
 5 years ago
Best ResponseYou've already chosen the best response.0hmm how abt ab???? is it ab?

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0first find ab = ba then multiply it by () = (ba) = ab LOL it's the same thing :)

angela210793
 5 years ago
Best ResponseYou've already chosen the best response.0^_^ Tjnx a lot :):):) ^_^

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0For equations having terms with absolute value, you have to calculate twice, once if the value inside the brackets is positive (nonnegative in a broader sense), and then if the value inside the brackets is negative. So, you have to think about cases, when (ab)<0, when 0<=(ab)<=1 and when (ab)>1. Now the solution. 1st case: when (ab)<0 or a<b, ab = ba. And, 1a+b = 1(ab) = 1a+b. ba = ba. So, the simplification will be 1/b. 2nd case: when 0<=(ab)<=1, then ab = ab, 1a+b = 1(ab) = 1a+b. ba = ab. So the simplification will be (12a+2b)/(2ab). 3rd case: when (ab)>1, then ab = ab, 1a+b = 1(ab) = ab1, ba = ab. So the simplification will be 1/(b2a). Enjoy. :)

angela210793
 5 years ago
Best ResponseYou've already chosen the best response.0Oh thanks a lot :):):)
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.